The Art of Educating Hyperactive Children at an Early Age: How Do Teachers Act? - Putri, Rahmita; Kasman, Lusia; Syamsuddin; Akmal, Fauzy (Journal of Islamic Early Childhood Education, 2024)
The research problem in this thesis is that the author observed that children at the school had learning difficulties, were not focused, could not sit still in class, were easily irritated due to hyperactivity (ADHD). The purpose of this study was to find out 1. what methods are applied by teachers 2. what factors influence teachers to improve learning for hyperactive children 3. what obstacles do teachers face to improve learning for hyperactive children. The type of research is qualitative research, because this study produces qualitative descriptive data that describes Field research was conducted by exploring data sourced from teachers. Data collected through observation, interview and documentation techniques. Based on the results of the study, it can be concluded that 1. The teacher's method in guiding hyperactive children is to appreciate every effort and success achieved by the child 2. Factors that influence teachers to improve learning, the first is placing a seat close to the teacher, making physical contact such as eye contact, patting the shoulder. 3. The teacher's obstacle in guiding hyperactive children is that their focus is easily diverted